Signal-averaged electrocardiogram in chronic Chagas' heart disease - Moraes,Aguinaldo Pereira de (1995)
The aim of the study was to register the prevalence of late potentials (LP) in patients with chronic Chagas' heart disease (CCD) and the relationship with sustained ventricular tachycardia (SVT). 192 patients (96 males), mean age 42.9 years, with CCD were studied through a Signal Averaged ECG using time domain analysis. According to presence or absence of bundle branch block (BBB) and SVT, four groups of patients were created: Group I (n = 72): without SVT (VT-) and without BBB (BBB-): Group II (n = 27): with SVT (VT+) and BBB-; Group III (n = 63): VT- and with BBB (BBB+); and Group IV (N = 30): VT+ and BBB+. The LP was admitted, with 40 Hz filter, in the groups without BBB using standard criteria of the method. In the group with BBB, the root-mean-square amplitude of the last 40 ms (RMS) < =14µV was considered as an indicator of LP. RESULTS: In groups I and II, LP was present in 21 (78%) of the patients with SVT and in 22 (31%) of the patients without SVT (p < 0.001), with Sensitivity (S) 78%; Specificity (SP) 70% and Accuracy (Ac) 72%. LP was present in 30 (48%) of the patients without and 20 (67%) of the patients with SVT, in groups III and IV. p = 0.066, with S = 66%; SP = 52%; and Ac = 57%. In the follow-up, there were 4 deaths unrelated to arrhythmic events, all of them did not have LP. Eight (29,6%) of the patients from group II and 4 (13%) from group IV presented recurrence of SVT and 91,6% of these patients had LP. CONCLUSIONS: LP occurred in 77.7% of the patients with SVT and without BBB. In the groups with BBB, there was association of LP with SVT in 66,6% of the cases. The recurrence of SVT was present in 21% of the cases from which 91,6% had LP.